2013
DOI: 10.1179/1607845412y.0000000068
|View full text |Cite
|
Sign up to set email alerts
|

The sticky platelet syndrome

Abstract: The sticky platelets syndrome (SPS) is a procoagulant condition based on either arterial, venous, or capillary thrombi caused by hyperesponsive and hyperaggregable platelets. This is a frequent disease, which often remains clinically inapparent, until stressful events or combination with other factors increase the risk of developing SPS. The condition is due to a congenital platelet defect with autosomal dominant characteristics, leading to the increased platelet aggregability when they are challenged with epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 15 publications
0
25
0
2
Order By: Relevance
“…In Mexico, we 6,26,27,33 and others 22,25 have found that approximately 50% of Mexican mestizo patients with a clinical maker of thrombophilia display the SPS phenotype. Most patients with the SPS display other thrombosis-prone conditions but there are also instances of the SPS identified as the single thrombophilia marker 6,26,27,33 . It is therefore possible that the SPS may contribute to the so-called ''multifactorial thrombophilia.''…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Mexico, we 6,26,27,33 and others 22,25 have found that approximately 50% of Mexican mestizo patients with a clinical maker of thrombophilia display the SPS phenotype. Most patients with the SPS display other thrombosis-prone conditions but there are also instances of the SPS identified as the single thrombophilia marker 6,26,27,33 . It is therefore possible that the SPS may contribute to the so-called ''multifactorial thrombophilia.''…”
Section: Discussionmentioning
confidence: 99%
“…[7][8] Up to now, no molecular substrate has been found to explain the platelet hyperaggregability in the SPS phenotype, this being the reason why only a few research groups have accepted this entity as a true thrombophilic condition. [29][30][31][32][33] Only a few attempts to correlate the SPS phenotype with molecular markers of platelet hyperaggregability have been described, the GP IIIa PL A1/A2 (HPA-1a/b ITGB3: c.196T>C) polymorphism 7,32 and the growth arrest-specific gene 6 (Gas6; Gas6: c.834þ7G>A) polymorphisms. 8 The treatment of the SPS relies on diminishing the platelet hyperaggregability by means of employing antiplatelet drugs 18,28,31,33 ; in most cases, aspirin is adequate to revert the phenomenon, 28 but there are instances in which other antiplatelet drugs must be employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycoprotein IIb/IIIa (GPIIb/IIIa), a heterodimeric platelet surface receptor consisting of the αIIb (CD41) and the β3 (CD61) subunits, [25], it has been for a long time primarily just a theoretical concept with little practical basis. Although the overall clinical picture of SPS, with its transient or permanent vascular occlusions, is well known, the pathophysiological mechanism of the syndrome remains unclear [10,11,26]. It was regarded as a frequent disease and the clinical symptoms, especially arterial thrombosis, often present following an emotional stress [5,6,11].…”
Section: Sps and Gpiiia Pla1/a2mentioning
confidence: 99%
“…The role of the demonstrated platelet hyperaggregability as a possible risk factor for venous thromboembolism is not well defined [1][2][3]7,8]. Some authors described an enhanced maximal platelet aggregation by platelet aggregometry as a contributing factor for arterial and venous thrombosis; naming this observation ''Sticky-Platelet Syndrome'' (SPS) [5,6,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%